Gender data for good? Partnerships between tech companies and humanitarian and development organizations - Tara Patricia Cookson; Ruth Carlitz (Big Data & Society)
In 2013, the United Nations called for a “Data Revolution” to advance sustainable development. “Data for Good” initiatives that have followed bring together development and humanitarian actors with technology companies. Few studies have examined the composition of Data for Good partnerships or assessed the uptake and use of the data they generate. We help fill this gap with a case study of Meta's (then Facebook) Survey on Gender Equality at Home, which reached over half a million Facebook users in more than 200 countries. The survey was developed in partnership with international development and humanitarian organizations. Our study is uniquely informed by our involvement in this partnership: we contributed subject matter expertise to the development of the survey and advised on dissemination strategies for the resulting data, which we also analyzed in our own academic work. We complement this autoethnographic perspective with insights from scholars of partnerships for development, and a practitioner framework to understand the factors connecting data to action. We find that including multiple partners can widen the scope of a project such that it gains breadth but loses depth. In addition, while it is (somewhat) possible to quantify the impact of a Data for Good partnership in terms of data use, “goodness” can also be assessed in terms of the process of producing data. Specifically, collaborations between organizations with different interests and resources may be of significant social value, particularly when they learn from one another—even if such goodness is harder to quantify.